DEVELOPMENT OF THE PROPOSED MICROLEARNING-BASED DYNAMIC INTELLECTUAL LEARNING SYSTEM TO ACTUALIZE AN EFFECTIVE LEARNING PROCESS IN ONLINE ENVIRONMENT - Marti, Ni Wayan; I Gusti Putu Suharta; Ketut Agustini; I Komang Sudarma; I Nyoman Saputra Wahyu Wijaya; Luh Putu Tuti Ariani (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The era of educational transformation in the 21st century is a stream of change where teachers and students simultaneously hold an important role in the learning process. In this matter, it is necessary to apply innovation and technology integration to realize an effective learning process. This study aims to build a dynamic intellectual learning system based on microlearning (DIL-MicLearn system) which is accessed via the web. This research uses a theoretical-descriptive-development method that uses theoretical studies, software development proses, and expert evaluation. The research phase used is the first two stages of the Plomp design research model, namely the Prelimentary Research stage, and the Development or Prototyping phase. The DIL-MicLearn system is a personalized learning system that allows students to achieve learning mastery in each learning unit according to their cognitive abilities and learning speed, can access learning content according to learning styles, and can reduce students' cognitive load in the learning process. The DIL-MicLearn system is implemented in a online learning environment, considering the characteristics of this system. The advantages and disadvantages of this system are described in detail. The validity level of the DIL-MicLearn system reaches 99.57% and this system is valid for use in the learning process.